Digitalization of precision fertilization in East Africa: adoption, benefits and losses - Fue, Kadeghe Goodluck; Baitu, Geofrey Prudence; Jokonya, Osden; Banwart, Steven; Korsten, Lise (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe rapid digitalization of agriculture in East Africa has spurred the adoption of precision fertilization tools, which optimize nutrient application and enhance crop yields. However, the extent of digital technology adoption, its benefits, and the challenges smallholder farmers face in the region remain unclear.MethodsA systematic review adhering to PRISMA guidelines assessed the adoption of digital technologies for precision fertilization in East Africa. A comprehensive search of English-language studies published between 2010 and 2024 resulted in fifteen studies that met the inclusion criteria.ResultsThe review highlights digital solutions that assist smallholder farmers in sustainable resource management, including mobile applications, ICT tools, Variable Rate Application (VRA), and AI/ML technologies. Reported benefits include improved crop productivity, increased economic efficiency, and enhanced environmental sustainability. However, issues with data accuracy, limited access to technology, affordability constraints, and low digital literacy hinder widespread adoption.DiscussionThe findings emphasize the need for further research and the development of tailored strategies to enhance digital agricultural practices in East Africa. Addressing socioeconomic and infrastructure challenges is crucial to ensuring equitable access and maximizing the effectiveness of digital precision fertilization tools. This review provides valuable insights to support stakeholders in developing sustainable, data-driven agricultural frameworks to improve regional food security.